1997
DOI: 10.1016/s0020-7292(97)00084-2
|View full text |Cite
|
Sign up to set email alerts
|

Gestational and pre‐gestational diabetes: comparison of maternal and fetal characteristics and outcome

Abstract: The incidence of maternal, fetal and neonatal complications in GDM is similar to pre-GDM patients and their offspring. Both GDM and pre-GDM pregnancies and the offspring should, therefore, be monitored and managed identically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 17 publications
10
39
0
2
Order By: Relevance
“…[7] Another study of 972 GDM mothers in Saudi Arabia showed that the common complications were perineal tear (18%) that caused postpartum hemorrhage, followed by gestational hypertension (2%). [14]…”
Section: Discussionmentioning
confidence: 99%
“…[7] Another study of 972 GDM mothers in Saudi Arabia showed that the common complications were perineal tear (18%) that caused postpartum hemorrhage, followed by gestational hypertension (2%). [14]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown high rates of caesarean delivery in women with GDM than in their nondiabetic counterparts (18,(27)(28)(29)(30). In a retrospective cohort study of 874 U.S. women with class A1 GDM, Casey et al (31) reported a significantly higher caesarean delivery in these women compared with the general obstetric population (30 vs. 17%).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal demographics, OGTT and Hb results, pregnancy complications and infant outcome were compared between the groups with and without the athalassaemia trait. The pregnancy complications we examined included caesarean section [20±22], pre-eclampsia [20±22], antepartum haemorrhage [22], and preterm birth [21]. For infant outcome, large-for-gestational age (LGA) is defined as birthweight above the 90th percentile for gestational age in our local population according to our standardised chart.…”
Section: Methodsmentioning
confidence: 99%